2008
DOI: 10.1504/ijtmkt.2008.019922
|View full text |Cite
|
Sign up to set email alerts
|

Product development in the automotive industry: crucial success drivers for technological innovations

Abstract: Abstract:Developing new innovative products in the automotive industry means investing huge sums in advance, as one does not know if the product will be successful on the market after launch. Hence, companies are interested in knowing and measuring the critical success drivers within the development steps. The paper discusses the results of a qualitative meta-analysis of 16 empirical studies on New Product Development (NPD) success, which was carried out to gain deeper insight into these success drivers. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 55 publications
2
6
0
1
Order By: Relevance
“…Depending on the situation, engineers are also able to identify the requirements and are active in this stage, and not just in realizing functions. These findings are in line with the studies on lead-user studies (Bilgram, Brem, & Voigt, 2008;Brem & Bilgram, 2015;Gerhard, Brem, & Voigt, 2008) and…”
Section: Prototyping Activitiessupporting
confidence: 91%
See 1 more Smart Citation
“…Depending on the situation, engineers are also able to identify the requirements and are active in this stage, and not just in realizing functions. These findings are in line with the studies on lead-user studies (Bilgram, Brem, & Voigt, 2008;Brem & Bilgram, 2015;Gerhard, Brem, & Voigt, 2008) and…”
Section: Prototyping Activitiessupporting
confidence: 91%
“…Yasar (2007) including, but not limited to, the use of prototypes. These findings are in line with the studies on lead-user studies (Bilgram, Brem, & Voigt, 2008;Brem & Bilgram, 2015;Gerhard, Brem, & Voigt, 2008) and In addition to those descriptions, we found that designers also have interest in user experience studies and take them into consideration in prototype development; in this case, users, instead of testing the prototype at the end, get involved at an earlier stage.…”
Section: Prototyping Activitiessupporting
confidence: 89%
“…Considering the above, this study has focused on SMMS to portray how specialized SMEs are also adopting and implementing OI to a great extent, allowing them to survive in a highly competitive mature industry (Gerhard et al, 2008). Therefore, the general findings of this study contribute to the shift urged in the OI literature of avoiding potential misleading general prescriptions and instead providing more focused implications for OI research and practice (Tidd, 2014).…”
Section: Theoretical Contributionmentioning
confidence: 92%
“…Also, SMEs' internal R&D activities together with particular OI practices can play a direct and critical role in a firm's innovation output and thus its level of innovativeness (Cheng and Huizingh, 2014;Kim and Park, 2010). This is specially true in the automotive industry where an internal lack of adequate R&D skills to successfully drive new radical product development would force a firm to obtain these skills from external partners (Gerhard et al, 2008). In line with the above, while some particular inbound practices in SMEs can be linked to radical innovation outputs, others are linked to incremental innovation levels (Parida et al, 2012).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The most common mode of technology management is the internal R&D management. Internal development contributes to build up knowledge, which is especially important for core technologies, which are part of the company's strategic orientation and, consequently, its success [Gerhard et al (2008)]. Especially if the company intends to be a technology leader in a certain area, internal expertise is crucial.…”
Section: Generic Alternatives For Technology Sourcingmentioning
confidence: 99%